Constructal theory of global circulation and climate - Reis, A. Heitor (2006)
The constructal law states that every flow system evolves in time so that it develops the flow architecture that maximizes flow access under the constraints posed to the flow. Earlier applications of the constructal law recommended it as a self-standing law that is distinct from the second law of thermodynamics. In this paper, we develop a model of heat transport on the earth surface that accounts for the solar and terrestrial radiation as the heat source and heat sink and with natural convection loops as the transport mechanism. In the first part of the paper, the constructal law is invoked to optimize the latitude of the boundary between the Hadley and the Ferrel cells, and the boundary between the Ferrel and the Polar cells. The average temperature of the earth surface, the convective conductance in the horizontal direction as well as other parameters defining the latitudinal circulation also match the observed values. In the second part of the paper, the constructal law is invoked in the analysis of atmospheric circulation at the diurnal scale. Here the heat transport is optimized against the Ekman number. Even though this second optimization is based on very different variables than in the first part of the paper, it produces practically the same results for the earth surface temperature and the other variables. The earth averaged temperature difference between day and night was found to be approximately 7 K, which matches the observed value. The accumulation of coincidences between theoretical predictions and natural flow configuration adds weight to the claim that the constructal law is a law of nature.